Photoelectrochemical water splitting using one-dimensional nanostructures - Lee, Joo-Won; Cho, Ki-Hyun; Yoon, Joon-Soo; Kim, Young-Min; Sung, Yun-Mo (Royal Society of Chemistry, 2021)
Hydrogen energy is an attractive alternative to fossil fuels. Among the various methods for H-2 production, solar-driven photoelectrochemical (PEC) water splitting is considered as the representative technique because of its ecofriendly process and the abundance of resources. To achieve higher PEC performance, one-dimensional (1D) nanostructures have been highlighted owing to their considerable potential as photocatalyst materials. Not only the enhanced surface area, but also the unique and novel properties ascribed to their anisotropic characteristics have allowed enhanced PEC performance compared to thin-film photoelectrodes. In this manuscript, we review the recent research on 1D nanostructured photoelectrodes for solar-driven PEC water splitting. The brief synthetic approaches to develop 1D nanostructured photoelectrodes and various strategies to improve their performance are summarized, which can provide a roadmap on the development of advanced photoelectrodes for H-2 generation.